2020
DOI: 10.5507/bp.2019.055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine versus remifentanil on mothers and neonates during cesarean section under general anesthesia

Abstract: Background and Aims. Dexmedetomidine and remifentanil use in obstetric general anesthesia is controversial. This study aimed to compare the effects of remifentanil and dexmedetomidine on mothers and neonates during cesarean section under general anesthesia. Methods. A total of 120 patients scheduled for elective cesarean section under general anesthesia were randomly allocated to dexmedetomidine (D), remifentanil (R), and control (C) groups. Anesthesia was induced with propofol and muscle relaxants in all grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The subsequent resumption of spontaneous breathing allows the patient to be removed early after surgery without causing respiratory depression. However, the increase of blood pressure during endotracheal intubation and surgical stimulation can be inhibited by remifentanil and mainly manifested as dose-dependent decline in blood pressure and heart rate [ 14 , 15 ]. The effect of using remifentanil commonly occurs dilating blood vessels and slowing heart rate resulting in bradycardia during anesthesia, while the symptoms of bradycardia disappear after anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent resumption of spontaneous breathing allows the patient to be removed early after surgery without causing respiratory depression. However, the increase of blood pressure during endotracheal intubation and surgical stimulation can be inhibited by remifentanil and mainly manifested as dose-dependent decline in blood pressure and heart rate [ 14 , 15 ]. The effect of using remifentanil commonly occurs dilating blood vessels and slowing heart rate resulting in bradycardia during anesthesia, while the symptoms of bradycardia disappear after anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, cTnI is a highly sensitive and specific biomarker in the diagnosis of myocardial injury in the clinic (31). In addition, Dex inhibits the release of catecholamines to reduce HR (32), which prolongs coronary perfusion and simultaneously reduces myocardial oxygen consumption, thus improving the maintenance of the myocardial oxygen supply-demand balance (33,34). Dex is also able to increase the ischemic to non-ischemic myocardial blood flow ratio during myocardial ischemia in the perioperative period (35,36).…”
Section: Discussionmentioning
confidence: 99%
“… 152 Another report indicated that during general anesthesia for cesarean section, although remifentanil demonstrated better control of hemodynamic stability, dexmedetomidine rather demonstrated better neonatal Apgar scores, postoperative analgesia, and decreased catecholamine release. 139 However, other studies have reported no significant difference in the effect of dexmedetomidine and remifentanil on maternal hemodynamics and bi-spectral index, and neonatal outcomes in elective cesarean delivery, although remifentanil still has the potential to cause neonatal transient respiratory depression. 153 …”
Section: Comparative Studies With Other Agentsmentioning
confidence: 97%
“… 138 An assessment of its effect on both the mothers and neonates during cesarean section under general anesthesia indicates that dexmedetomidine presents better neonatal Apgar scores, postoperative analgesia, and decreased catecholamine release. 139 Moreover, the use of dexmedetomidine in the perioperative period of cesarean section is not only conducive to the early conversion of infant feeding to exclusive breastfeeding but can also enhance the recovery quality and comfort of the parturient, optimize analgesia, reduce the time to the first lactation, and increase lactation. 140 …”
Section: Key Surgical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation